A Pilot Study on a Smart Home for Elders Based on Continuous In-Home Unobtrusive Monitoring Technology. (July 2019) - Yu, Jingyu; An, Ning; Hassan, Tanbir; Kong, Quan
Purpose: This article reports on a pilot study of a smart home for elders (SHfE) designed to continuously monitor senior adults' daily behaviors and the living environment of their residential homes using the application of unobtrusive sensors. SHfE users include older adults, their family members, and healthcare staff. Background: Globally, countries are experiencing the challenges of an increasingly aging population. A healthy environment is essential to support aging in place. By applying information and communications technology to building environments to support health, smart homes may be an option to provide a low-cost, comfortable, and user-friendly living environment for older adults. Method: A pilot study was conducted in a capital city in the Yangtze River Delta Agglomerations in China to verify the feasibility of the SHfE. One female older adult participated in the pilot study, which was conducted from November 2015 to January 2016. Results: The results indicated that the SHfE is a feasible way to analyze the behaviors (e.g., sleeping, cooking, water usage) of the elder and monitor the built environment (e.g., temperature, windows, and doors). Conclusions: The pilot study can be used as a baseline for further comprehensive experiments, case studies, and surveys to gain a better understanding of a smart healthy environment for older adults. On the basis of the current study, several recommendations are put forward for further implementation of the SHfE, including integrating multiple unobtrusive sensing devices; detecting fall accidents; monitoring indoor lighting, noise, and ventilation; remotely controlling electrical appliances; and developing the system with various languages. It is anticipated that the SHfE will be adopted in seniors' residential homes in countries around the world which face an increasingly aging population.